Correlation of arbuscular mycorrhizal dosage with level of colonization, nutrient concentration, and photosynthesis pigment of Cavendish banana plant - Akib, Muhammad Akhsan; Ilmi, Nur; Risnawati, Risnawati; Prayudyaningsih, Retno; Syatrawati, Syatrawati (Kultivasi, 2024)
The commercial development of Cavendish bananas still faces many obstacles, including the availability of seedlings/suckers at low prices, so technological substitution is needed to stimulate the growth of Cavendish banana suckers in the form of arbuscular mycorrhizal (AM) biological agents. The research aims to determine the correlation between AM doses and colonization levels, tissue nutrient concentrations, and photosynthetic pigments in Cavendish banana seedlings/suckers. It is also a novelty in this research study. The research was carried out in Parepare city at coordinates 3°59'30.204" S; 119°38'42.936" E using four AM doses as independent variables, namely 0 g, 5 g, 10 g, and 15 g pot-1.  The variables observed (dependent variables) were the level of colonization, nutrient concentration in the tissue, and photosynthetic pigment content. Using Microsoft Excel software, statistical tests, regression, and correlation analyses were conducted to see the relationship between treatment (independent variable) and observed parameters (dependent variable). The research showed that AM dosage was positively correlated with the level of root colonization, the concentration of N, P, and K elements in the tissue, and the photosynthetic pigments (chlorophyll a, chlorophyll b, and carotenoids). A dose AM of 15 g pot-1 gave a better effect on Cavendish banana suckers, which can be recommended for the development of Cavendish banana seedlings.